Synergistic antimicrobial activity of two binary combinations of marjoram, lavender, and wild thyme essential oils. Issue 12 (2nd December 2017) - Ouedrhiri, Wessal; Mounyr, Balouiri; Harki, El Houssaine; Moja, Sandrine; Greche, Hassane
ABSTRACT: The combination of essential oils (EOs) is a novel alternative to improve their preservative effects and to reduce their organoleptic impact in food. In this context, this work aims to investigate the antibacterial combined effect of two EOs combinations through the calculation of the fractional inhibitory concentration index. The combinations tested consists of Lavandula dentata/Origanum majorana EOs and Thymus serpyllum/Origanum majorana EOs. Their chemical compositions were identified by CG/MS analyses. The main compounds of O. majorana EO were (-) - terpinene-4-ol and trans-4-thujanol. Those of L. dentata EO were β-pinene and 1, 8-cineole, and those of T. serpyllum EO were p-cymene and γ-terpinene. Regarding the outcomes, results highlighted partial synergistic and additive interactions. Two combinations of marjoram and thyme EOs had antibacterial activities against S. aureus . The first one corresponded to the quarter of the minimum inhibitory concentration of marjoram and half that of thyme. The second one was the mix of half and quarter of the minimum inhibitory concentration of respectively marjoram and thyme EOs. This last combination also showed an antibacterial effect against E. coli. The quarter and the half of their minimum inhibitory concentration of marjoram and lavender combination, respectively, gave a partial synergy against both strains. Henceforth, these findings could be largely exploited in food preservation through the use of minimal doses of these plant products without affecting the antibacterial and the organoleptic properties in foods.